A CASE STUDY ON TRIPLE TALAQ AND STATUS OF WOMEN IN INDIA - Tomar, Ekta (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This case study explores the practice of Triple Talaq (instant divorce) and its implications on the status of women in India. Triple Talaq, the practice where a Muslim man could divorce his wife by pronouncing the word "talaq" three times, has been a subject of intense legal, social, and political debate in India. The case study delves into the historical background, legal battles, and societal impacts of Triple Talaq, with a focus on its consequences for women’s rights, their social standing, and their economic empowerment. The study examines the role of Indian law in protecting women's rights, and it highlights the landmark judgment by the Indian Supreme Court that declared Triple Talaq unconstitutional in 2017. The analysis further sheds light on the broader implications of gender equality in India and the need for progressive reforms to ensure the empowerment and equal treatment of women in society.